From mosques to khanqahs: the origins and rise of Sufi institutions - Spahic, Omer (Universiti Sains Malaysia Press, 2014)
This paper examines the theme of the evolution of Sufi institutions from the realm of the mosque institution to independent and self-governing bodies and establishments which catered to the needs of the ever-proliferating Sufi community. The relationship between Sufi institutions and other Islamic socio-political, educational and religious institutions is also discussed. The focus of the paper, firstly, is on the historical Sufi needs which called for the creation of self-governing Sufi institutions. That is followed by discussing the Sufi notion of travel and how much such an important Sufi tradition facilitated the gradual emergence of Sufi institutions. Then, the emergence of Sufi institutions from simple duwayrahs (small houses or convents) to ribats and multipurpose khanqah complexes, are examined.